Electrotransfer of siRNA to Silence Enhanced Green Fluorescent Protein in Tumor Mediated by a High Intensity Pulsed Electromagnetic Field - Simona Kranjc Brezar; Matej Kranjc; Maja Čemažar; Simon Buček; Gregor Serša; Damijan Miklavčič (Vaccines, 2020)
The contactless high intensity pulsed electromagnetic field (HI-PEMF)-induced increase of cell membrane permeability is similar to conventional electroporation, with the important difference of inducing an electric field non-invasively by exposing a treated tissue to a time-varying magnetic field. Due to the limited number of studies in the field of electroporation induced by HI-PEMF, we designed experiments to explore the feasibility of such a contactless delivery technique for the gene electrotransfer of nucleic acids in tissues in vivo. By using HI-PEMF for gene electrotransfer, we silenced enhanced green fluorescent protein (EGFP) with siRNA molecules against EGFP in B16F10-EGFP tumors. Six days after the transfer, the fluorescent tumor area decreased by up to 39% as determined by fluorescence imaging in vivo. In addition, the silencing of EGFP to the same extent was confirmed at the mRNA and protein level. The results obtained in the in vivo mouse model demonstrate the potential use of HI-PEMF-induced cell permeabilization for gene therapy and DNA vaccination. Further studies are thus warranted to improve the equipment, optimize the protocols for gene transfer and the HI-PEMF parameters, and demonstrate the effects of HI-PEMF on a broader range of different normal and tumor tissues.